Sociological knowledge and transformation at ‘Diversity University’ - Jenkins, Celia; Barnes, Caroline; McLean, Monica; Abbas, Andrea; Ashwin, Paul (Palgrave MacMillan, 2017)
Diversity University’ is a large university in London, UK, which appears in the bottom-third of national league tables and provides education for poorer students, often from ethnic minority groups. The Sociology Department at Diversity was the focus of research exploring quality and inequality in undergraduate degrees and here, with concrete examples, we discuss how its curriculum and pedagogy can be conceptualised as socially just. Concepts drawn from the work of the sociologist of education Basil Bernstein are employed to justify challenging students to make the necessary effort to bring difficult, abstract sociological knowledge into juxtaposition with everyday problems of life and society. In this way, tutors offer a quality of education that is equivalent to any in high-status universities;and, by way of knowledge acquisition, support relatively disadvantaged students to access what Bernstein calls ‘pedagogic rights’ to individual enhancement, social inclusion and political participation.